Biophysical and Biochemical Characterization and Plant Species Studies - Thenkabail, Prasad S.; Lyon, John G.; Huete, Alfredo; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Written by leading global experts, including pioneers in the field, the four-volume set on Hyperspectral Remote Sensing of Vegetation, Second Edition, reviews existing stateof- the-art knowledge, highlights advances made in different areas, and provides guidance for the appropriate use of hyperspectral data in the study and management of agricultural crops and natural vegetation. Hyperspectral remote sensing or imaging spectroscopy data has been increasingly used in studying and assessing the biophysical and biochemical properties of agricultural crops and natural vegetation. Volume III, Biophysical and Biochemical Characterization and Plant Species Studies demonstrates the methods that are developed and used to study terrestrial vegetation using hyperspectral data. This volume includes extensive discussions on hyperspectral data processing and how to implement data processing mechanisms for specific biophysical and biochemical applications such as crop yield modeling, crop biophysical and biochemical property characterization, and crop moisture assessments. The concluding chapter provides readers with useful guidance on the highlights and essence of Volume III through the editors perspective. Key Features of Volume III: Covers recent abilities to better quantify, model, and map plant biophysical, biochemical water, and structural properties. Demonstrates characteristic hyperspectral properties through plant diagnostics or throughput phenotyping of plant biophysical, biochemical, water, and structural properties. Establishes plant traits through hyperspectral imaging spectroscopy data as well as its integration with other data, such as LiDAR, using data from various platforms (ground-based, UAVs, and earth-observing satellites) Studies photosynthetic efficiency and plant health and stress through hyperspectral narrowband vegetation indices. Uses hyperspectral data to discriminate plant species and\or their types as well as their characteristics, such as growth stages. Compares studies of plant species of agriculture, forests, and other land use\land cover as established by hyperspectral narrowband data versus multispectral broadband data. Discusses complete solutions from methods to applications, inventory, and modeling considering various platform (e.g., earth-observing satellites, UAVs, handheld spectroradiometers) from where the data is gathered. Dwells on specific applications to detect and map invasive species by using hyperspectral data.
Section I: Vegetation Biophysical and Biochemical Properties 1. Recent Developments in Remote Estimation of Crop Biophysical and Biochemical Properties at Various Scales [Anatoly A. Gitelson] 2. Hyperspectral Assessment of Ecophysiological Functioning for Diagnostics of Crops and Vegetation [Yoshio Inoue, Roshanak Darvishzadeh, and Andrew Skidmore] 3. Spectral and Spatial Methods for Hyperspectral and Thermal Image-Analysis to Estimate Biophysical and Biochemical Properties of Agricultural Crops [Yafit Cohen and Victor Alchanatis] 4. Spectral and 3D Nonspectral Approaches to Crop Trait Estimation Using Ground and UAV Sensing [Helge Aasen and Georg Bareth] 5. Photosynthetic Efficiency and Vegetation Stress [Elizabeth M. Middleton, K. Fred Huemmrich, Qingyuan Zhang, Petya K.E. Campbell, and David R. Landis] Section II: Plant Species Identification and Discrimination 6. Crop Type Discrimination Using Hyperspectral Data: Advances and Perspectives [Lnio Soares Galvo, Jos Carlos Neves Epiphanio, Fbio Marcelo Breunig, and Antnio Roberto Formaggio] 7. Identification of Canopy Species in Tropical Forests Using Hyperspectral Data [Matthew L. Clark] 8. Characteristics of Tropical Tree Species in Hyperspectral and Multispectral Data [Matheus Pinheiro Ferreira, Cibele Hummel do Amaral, Gaia Vaglio Laurin, Raymond Kokaly, Carlos Roberto de Souza Filho, and Yosio Edemir Shimabukuro] 9. Detecting and Mapping Invasive Plant Species Using Hyperspectral Data [Ruiliang Pu] 10. Visible, Near Infrared, and Thermal Spectral Radiance On-Board UAVs for High-Throughput Phenotyping of Plant Breeding Trials [Scott C. Chapman, Bangyou Zheng, Andries B. Potgieter, Wei Guo, Frederic Baret, Shouyang Liu, Simon Madec, Benoit Solan, Barbara George-Jaeggli, Graeme L. Hammer, and David R. Jordan] Section III: Conclusions 11. Fifty Years of Advances in Hyperspectral Remote Sensing of Agriculture and VegetationSummary, Insights, and Highlights of Volume III: Biophysical and Biochemical Characterization and Plant Species Studies [Prasad S. Thenkabail, John G. Lyon, and Alfredo Huete].
Includes bibliographical references and index.
Also available in print format.
Keywords: SCIENCE / Earth Sciences / General; TECHNOLOGY & ENGINEERING / Agriculture / General; Broad-band data from sensors; Landsat ETM+.; Cloud computing; Crop water use and water productivity modeling and mapping; Hyperspectral sensor systems; Spaceborne hyperspectral EO-1 Hyperion pre-processing.; UAV and field hyperspectral data; Vegetation monitoring; Plants -- Remote sensing; Crops -- Remote sensing; Multispectral imaging; Electronic books